Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian pada Toko Vivi Jilbab di Sungai Kambang Jambi - Sarsabillah Sarsabillah; Habriyanto Habriyanto; Nova Erliyana (YASIN, 2026)
The rapid development of the Muslim fashion industry in Indonesia has intensified competition among local hijab businesses, making it necessary for business actors to understand the factors that influence consumers’ purchasing decisions. However, studies that specifically examine the effects of product quality and price on local Muslim fashion businesses remain relatively limited. This study aims to analyze the effects of product quality and price on consumers’ purchasing decisions at Toko Vivi Jilbab Sungai Kambang Jambi. This study used a quantitative approach with a causal design. The research population consisted of 48,130 consumers, with a sample of 100 respondents determined using the Slovin formula and purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics 32. The results showed that product quality had a positive and significant effect on purchasing decisions (t = 5.439; p < 0.001), while price also had a positive and significant effect on purchasing decisions (t = 3.021; p = 0.003). Simultaneously, product quality and price had a positive and significant effect on purchasing decisions (F = 91.028; p < 0.001), with an Adjusted R² value of 0.645. Product quality was the most dominant factor influencing consumers’ purchasing decisions. The conclusion of this study affirms that purchasing decisions are formed through consumers’ evaluation of product benefits and the appropriateness of the prices offered. The implications of this study indicate the importance of maintaining product quality and implementing competitive pricing strategies to increase purchasing decisions and strengthen the competitiveness of local hijab businesses.